A series of chiral metal–organic frameworks based on fluorene di- and tetra-carboxylates: syntheses, crystal structures and luminescence properties. Issue 15 (24th March 2017) - Robin, Julien; Audebrand, Nathalie; Poriel, Cyril; Canivet, Jerôme; Calvez, Guillaume; Roisnel, Thierry; Dorcet, Vincent; Roussel, Pascal
Abstract : Chiral MOFs built from copper and fluorene-based optically pure ligands possess various topologies and porosities and present luminescence properties. Abstract : A series of optically pure carboxylate ligands based on a fluorene backbone were synthesized and used for the elaboration of four chiral metal–organic frameworks (6, 7, 8, and9 ) containing Cu-based paddle-wheels. The positions and numbers of coordinating carboxylate functions on the ligand core govern the resulting MOF topologies, leading to a 1D framework (8 ), 2D grids with (7 ) or without interpenetration (6 ), and a 3D (9 ) framework and showing calculated porosities ranging from 8 to 47% of the unit-cell volumes. Ligands as well as corresponding MOFs possess luminescence properties with blue emission. The most porous MOF (9 ), made of a tetracarboxylate ligand, exhibits a BET apparent surface area of 467 m 2 g −1 and methane and carbon dioxide storage capacities of 26.5 cm 3 g −1 and 129 cm 3 g −1, respectively, at 303 K and 30 bar.